Impact of educational stress on cortisol, cardiac autonomic drive and academic performance of medical students - Upadhayay, Namrata; Khadka, Rita; Paudel, Bishnu Hari (Asian Journal of Medical Sciences, 2014)
Objectives: To assess stressors, heart-rate variability (HRV) and cortisol level in first year medical students (n-85), thrice in a year (beginning vs. mid-year vs. end-year). And we examined the association of these variables with their academic performance. Methods: Stressors were measured by medical student stressor questionnaire (MSSQ). HRV was assessed in eye-closed awake resting state for 5-min by Polar S810i. The salivary cortisol was assayed by ELISA method. Data were compared by Wilcoxon-Sign Rank test. Spearman correlation was applied between measured variables. Data are expressed as median (quartile 1-quartile 3), and significance was set at p≤0.05. Results: On MSSQ, students perceived mild to moderate degree of stress. About 8.24% and 11.8% of students perceived severe degree of stress in academic and inter-intrapersonal related stressors, respectively. Degree of stress in the beginning of the study was significantly high as compared to other visits. It was positively correlated with decreased HRV (decreased vagal activity and increased sympatho-excitation), high cortisol but with better academic performance in the beginning of the study. Cortisol (ng/ml) was significantly high in the beginning as compared to other visits [6.33 (5.05-7.43) vs. 1.33 (1.32-1.37) vs. 5.94 (5.1-6.6)]. The HRV measures showed mirror image of the cortisol among the visits. Conclusion: Stress level is mild to moderate degree in first year medical students which decreased as the year ended. Biochemical markers of stress, cortisol and HRV have similar trend. DOI: http://dx.doi.org/10.3126/ajms.v5i4.9843 Asian Journal of Medical Sciences 2014 Vol.5(4); 73-78